Avoin Aperitiff kirjoituksia Kari Aronpuron kollaasiromaanista Aperitiff - avoin kaupunki - Helle, Anna; Piippo, Laura; Joensuu, Juri; Keskinen, Mikko (Tampere University Press, 2018)
This collection of critical essays concentrates on the renowned Finnish collage novel Aperitiff ‒ avoin kaupunki (Aperitiff, Open City) by Kari Aronpuro in its three editions (1965, 1978, 2015). The essays provide a theoretically wide-ranging and up-to-date introduction to Aperitiff but also to collage and the collage novel more generally. Aperitiff is approached from the viewpoints of source materials; information, media technologies, and conceptualism; facsimiles as images of writing; methodological and thematic humour and comedy; Situationist reading strategies; realist and neorealist cinema; and Aperitiff's relation to the contemporary Finnish experimental novel, especially to Neuromaani by Jaakko Yli-Juonikas. The collection also reprints Aronpuro's early essay on the reception of Aperitiff, and extracts from the typescript of the novel's second edition.